Finding cinderella ebook - Hoover, Colleen (Hopeless, 2013)
#1 New York Times bestselling author of It Starts with Us and It Ends With Us writes a free novella about the search for happily ever after. A chance encounter in the dark leads eighteen-year-old Daniel and the girl who stumbles across him to profess their love for each other. But this love has conditions: they agree it will only last one hour and it will only be make-believe. When their hour is up and the girl rushes off like Cinderella, Daniel tries to convince himself that what happened between them only seemed perfect because they were pretending it was perfect. Moments like that with girls like her don't happen outside of fairytales. One year and one bad relationship later, his disbelief in insta-love is stripped away the day he meets Six: a girl with a strange name and an even stranger personality. But Daniel soon realizes that fairytales don't exist, and unfortunately for Daniel, finding Cinderella doesn't guarantee their happily ever after...it only further threatens it.